Studi Literatur Pencegahan Bahaya Kebakaran pada Pemukiman Masyarakat Suku Baduy dan Penerapannya - Meta Vaniessa Tampubolon (Universitas Sebelas Maret Surakarta, 2020)
Cultural heritage areas in the form of historic urban villages are part of the country's wealth that deserves to be preserved. The value and authenticity of settlements is the focus of conservation measures. Protocol Hoi Ana in 2009 explained the dimensions of cultural heritage. This dimension is divided into two: first, dimensions that are visible, in the form of visual, visible, building material, location, place settings, and others. Second, the dimensions of values contained in cultural heritage, in the form of history, spirit of place and others. The authenticity and whereabouts of historic villages in a city have so far decreased in number and seem to disappear with frequent cases of fires that damage this cultural heritage area. From the data collected, there are various causes of fires in the historic urban village. The main focus is related to the low level of public awareness, among others: negligence due to the fall of candles, transformer explosions, excessive use of currents, low awareness of the causes of electricity theft practices which often lead to short circuits which cause fires that cause casualties, damage to urban areas and historical buildings in it. The historic city village is a property of the nation and state. The community has the same responsibility in a community to save and preserve it. This paper reviews various literature studies related to the role of the community in preventing the danger of fire in cultural heritage areas that have been home to tens or even hundreds of years. With the existence of knowledge and sense of ownership by the community, it is hoped that fire prevention management in the historic township can be applied and its sustainability carried out.